Evaluation of root fracture in permanent teeth according to season - Dogan, Mehmet S.; Kusdhany, Lindawati S.; Maharani, Diah A.; Callea, Michele; Yavuz, Izzet (Journal of Stomatology, 2017)
Aim of the study. Root fractures which occur as a result of dental trauma may change according to school and holiday periods, and seasons. The aim of our study was to evaluate their incidence as dental trauma based on seasonal variation in children between 8-15 years of age. Material and method. This epidemiological study was performed on 76 children patients who sustained root fracture. Root fractures were diagnosed using cone beam computed tomography and conventional radiography. The incidence of root fracture was examined and compared according to the seasons when patients presented for treatment. The study’ data were applied to chi-square test. Results. As a result of our study, it was found that root fractures often occur in winter and in males rather than females. When the distribution of root fractures in boys and girls is examined according to season, it is noted that